(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to identify the productive thinking of the students of the Kindergarten Department, and the research relied on the descriptive approach. The research sample was (200) students from the Kindergarten Department in the College of Basic Education / Al-Mustansiriyah University. Based on previous theories and studies related to the subject of their research, as the measure of productive thinking in its final form included (29) items. The researchers verified the psychometric properties of the tool, and the researchers reached the following results: - The students of the Kindergarten Department have productive thinking, as the results came with an arithmetic mean higher than the hypothetical mean of the scale